2019
DOI: 10.1029/2019gl082254
|View full text |Cite
|
Sign up to set email alerts
|

Snowmelt‐Triggered Earthquake Swarms at the Margin of Long Valley Caldera, California

Abstract: Fluids are well known to influence earthquakes, yet rarely are earthquakes convincingly linked to precipitation. Weak modulation or limited data often leads to ambiguous interpretations. In contrast, here we find that shallow seismicity in the Sierra Nevada range near Long Valley Caldera is strongly modulated by snowmelt. Over 33 years, shallow seismicity rates were ~37 times higher during very wet periods versus very dry periods. Relative earthquake relocations from a swarm in 2017 reveal downward migration f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…This mechanism could be responsible for the observed alternating pattern of rapid outward and slower inward motion at GNSS stations on the southwestern rim of LVC. In this interpretation, the amplitude of the horizontal deformation would correlate with the amplitude of seasonal groundwater‐level fluctuations (<2 m in dry years and >10 m in wet years, Montgomery‐Brown et al, ) and the deformation would preferentially occur in typically highly fractured areas around the caldera (Acocella, ; Walter & Motagh, ; Wang et al, ). Interestingly, the largest horizontal amplitude occurs at station MINS, which moves in southwest direction in spring/summer and lies on the west side of Mammoth Mountain, one of the main infiltration areas of LVC hydrothermal system (Pribnow et al, ; Peacock et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This mechanism could be responsible for the observed alternating pattern of rapid outward and slower inward motion at GNSS stations on the southwestern rim of LVC. In this interpretation, the amplitude of the horizontal deformation would correlate with the amplitude of seasonal groundwater‐level fluctuations (<2 m in dry years and >10 m in wet years, Montgomery‐Brown et al, ) and the deformation would preferentially occur in typically highly fractured areas around the caldera (Acocella, ; Walter & Motagh, ; Wang et al, ). Interestingly, the largest horizontal amplitude occurs at station MINS, which moves in southwest direction in spring/summer and lies on the west side of Mammoth Mountain, one of the main infiltration areas of LVC hydrothermal system (Pribnow et al, ; Peacock et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…All raw data are available from public databases: GNSS data are available at the USGS website (https://earthquake.usgs.gov/monitoring/gps/stations), precipitation and temperature data at the NOAA website (https://www.ncdc.noaa.gov/cdo-web), stream discharge data at the USGS National Water Information System website (https://waterdata.usgs.gov/ca/nwis), and lakes level data at the following sites (https://www.monolake.org/today/water, https://maps.waterdata.usgs.gov/, and https://cdec.water.ca.gov/cdecstation2/?sta=BIS). The Convict Lake swarm seismicity data are from Montgomery‐Brown et al () and based on the catalog data of the Northern California Earthquake Data Center (doi:10.7932/NCEDC). Figures have been produced by using the Generic Mapping Tools (GMT) software (Wessel et al, ) and MATLAB software.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a small perturbation of the stress field due to fluid diffusion can likely trigger earthquakes. Some examples include seasonal modulation of the seismicity due to hydrological unloading (Carlson et al, 2020;Christiansen et al, 2007;Johnson et al, 2017), triggering earthquakes due to tides (Tanaka et al, 2002;Wilcock, 2001) and induced seismicity due to pore-pressure change by seasonal snowmelt (Montgomery-Brown et al, 2019;Saar & Manga, 2003). Several studies suggested that a pore-pressure increase of 0.01-0.1 MPa can trigger seismicity (Harris, 1998;Roeloffs, 1996;Stein et al, 1992Stein et al, , 1994.…”
Section: Critical Stress Changementioning
confidence: 99%
“…Seismicity induced by wastewater disposal in the U.S. midcontinent is one example (e.g., Ellsworth, ). In a recent and dramatic natural example, shallow seismicity in the Sierra Nevada near Long Valley Caldera, California—a high‐threat volcanic area—was shown to be strongly modulated by snowmelt, with seismicity rates ~37 times higher during very wet periods versus very dry periods (Montgomery‐Brown et al, ).…”
Section: Implications For Groundwater and Other Subsurface Resourcesmentioning
confidence: 99%